2010
DOI: 10.1039/c001483d
|View full text |Cite
|
Sign up to set email alerts
|

Unusual magnetic properties of a two-coordinate heteroleptic linear cobalt(ii) complex

Abstract: The synthesis and characterization of two-coordinate cobalt(ii) complexes CoAr'(2) (1) and Ar'CoN(SiMe(3))(2) (2) (Ar' = C(6)H(3)-2,6-(C(6)H(3)-2,6-(i)Pr(2))(2)) are reported. The magnetic data for 2 show that it has an unexpectedly high mu(eff) of 5.65 mu(B) whereas the bent complex 1 has a significantly lower moment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 25 publications
4
39
0
Order By: Relevance
“…Indeed, this naphthyl configuration brings the hydrogen atom on C(15) into proximity with the Zn 2+ ion: Zn ⋅⋅⋅ C(15) 2.872(2) Å; c.f. [Co(2,6‐Dipp 2 C 6 H 3 ) 2 ], which has Co ⋅⋅⋅ C 2.878 Å9 (crystallographic van der Waals radii are 2.0 and 2.1 Å for Co and Zn, respectively) 45. Although this Zn ⋅⋅⋅ C distance is smaller than the sum of the van der Waals radii for these elements (3.8 Å), any interaction between the Zn and flanking naphthyl moieties is likely to be weak.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, this naphthyl configuration brings the hydrogen atom on C(15) into proximity with the Zn 2+ ion: Zn ⋅⋅⋅ C(15) 2.872(2) Å; c.f. [Co(2,6‐Dipp 2 C 6 H 3 ) 2 ], which has Co ⋅⋅⋅ C 2.878 Å9 (crystallographic van der Waals radii are 2.0 and 2.1 Å for Co and Zn, respectively) 45. Although this Zn ⋅⋅⋅ C distance is smaller than the sum of the van der Waals radii for these elements (3.8 Å), any interaction between the Zn and flanking naphthyl moieties is likely to be weak.…”
Section: Resultsmentioning
confidence: 99%
“…This ligand configuration also facilitates the formation of an intramolecular CH ⋅⋅⋅ π‐electron interaction between an aryl proton in the 7‐position of the C(7) ring and the centroid of the C(33) aryl ring of a naphthyl substituent (H(14) ⋅⋅⋅ centroid 2.8798(10) Å; C(14)H(14) ⋅⋅⋅ centroid 132.89(19)°, Figure 2) and a longer interaction between an aryl proton in the 2‐position of the C(33) ring and the centroid of the C(17) aryl ring of the naphthyl substituent [H(34) ⋅⋅⋅ centroid 3.0835(10) Å; C(34)H(34) ⋅⋅⋅ centroid=157.89(16)°) 46. 47 It is conceivable that such CH ⋅⋅⋅ π interactions could also contribute to the bending in the C‐Zn‐C moiety; Power and co‐workers have suggested that such interactions may contribute to the bent geometry at the cobalt(II) centre in [Co(2,6‐Dipp 2 C 6 H 3 ) 2 ],9 and the influence of these interactions on the conformation of solid‐state structures has been documented 47. Concomitant with this CH ⋅⋅⋅ π interaction, there is a slight deviation from planarity for the C(7) naphthyl ring (torsion angle 4.84(8)°) and the C(33) naphthyl ring (torsion angle 3.78(9)°) in 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations